Mapping Priority Areas for Forest Recovery using Multicriteria Analysis in the Brazilian Atlantic Forest - de Almeida, Franciane Carla; Silveira, Eduarda Martiniano de Oliveira; de Paiva, Lara Lopes; Júnior, Fausto Weimar Acerbi (Ra'e Ga: o Espaço Geográfico em Análise, 2019)
The collapse of a mining dam with 62 million cubic meters of mud in the Rio Doce basin resulted in the destruction of whole communities and large areas of Atlantic Forest. As forest restoration activities are among the most costly conservation strategies, prioritization of restoration efforts is crucial. In the present article, we mapped priority areas for forest recovery in a portion of the Rio Doce Basin (DO1) using a GIS-based (geographic information system) multicriteria decision analysis (MCDA) employing the weighted linear combination (WLC) method. Five factors with different weights were taken into consideration according to their level of importance: distance from the drainage network, distance from the native vegetation patches, slope, soil class and precipitation. A map of priority areas was produced where 1.73% of the area was classified as very high priority for forest recovery, while 5.18% of the area was classified as high priority, 57.88% as medium priority, 1.34% as low priority and 0.00% as very low priority. The highest weights were both for the distance from the drainage network and the distance from native vegetation, revealing that areas of permanent preservation and those closer to forest fragments are priority areas for forest recovery. MCDA is a flexible and easy-to-implement method generating maps with suitable solutions for forest recovery. The approach taken can be replicated in regions that require support for decision making in environmental planning, such as the Pantanal biome, which is under considerable pressure from deforestation for the expansion of pastures.